Delineation of contamination plumes through technological resources (Research, Society and Development, 2026)
The management of contaminated areas and the necessary post-spill treatments, especially of hydrocarbons, are essential in a society whose development has brought with it the use of these compounds. Cities like São Paulo, which have industrial parks that for many years operated with little or no regulation or oversight regarding the control of pollutants spilled on the ground, have an environmental liability that needs to be addressed in order to avoid greater impacts. In this sense, the present study aims to explore spatial visualization methods to assist in the study of these areas, regarding the spread of contaminants in the soil. An experimental, laboratory research was carried out in a quantitative approach study using mathematical modeling of phenomena with computational resources in the Python programming language. The model can be valid when the sampled points are previously known as the polluting sources or the points of highest concentration of the contaminant of interest, since it delimits the area of ​​influence of a region that is responsible for the propagation of the contaminant.